A Systematic Literature Review and Analysis of Mobile Retailing Adoption. Issue 2 (3rd April 2019) - Tyrväinen, Olli; Karjaluoto, Heikki
Abstract: The purpose of this study is to provide a comprehensive updated review and analysis of mobile retailing adoption. Although research on mobile channel utilization has increased significantly in recent years and many new studies on this topic have been published, research has not yet provided a clear structure regarding how consumers' expectations have advanced in relation to mobile retailing adoption. Thus, this study synthetizes the mobile retail adoption literature and develops a framework for it. Our systematic literature review analyzed 94 scientific articles that were published between 2010 and 2018 to determine customers' different expectations and demands during different mobile channel adoption stages. Our findings enhance the understanding of how retailers can serve customers in each stage. In addition, our framework provides opportunities and provokes questions for further research as well as shifts the focus from technology adoption-oriented topics toward customer journeys. Highlights: Customers' previous mobile shopping experience, their stage of mobile channel use, and the retailing context determine which features are the most valuable. In the initial stages of use, when customers are unfamiliar with mobile technologies and thus lack experience on mobile channels, they prefer utilitarian benefits. In later stages, when customers are familiar with mobile channels, they value more hedonic aspects. A mobile channel is not seen as a purchasing channel but rather as a searching channel. If retailers succeed in turning a mobile channel into a purchasing channel, they can provide deeper and more satisfying customer experiences.